Anxiety Among Juvenile Residents Prior to Release from the Class I A Special Child Development Institution in Kupang - Tokan, Marciany Cahyaratry Airlangga Putri; Marni, Marni; Manafe, Rizky Pradita (Ahmar Metastasis Health Journal, 2025)
Children in conflict with the law who undergo rehabilitation in the Special Child Development Institution (LPKA) face not only physical confinement but also serious psychological pressure. One of the most common psychological conditions that emerges prior to their release is anxiety, which is triggered by various factors such as loss of self-control, fear of social rejection, and uncertainty about the future. Without appropriate intervention, this anxiety may hinder the process of adaptation and social reintegration after release. Therefore, understanding the psychological condition of juvenile inmates—particularly during the transition period toward freedom—is essential. This study aims to describe the causes, forms, responses, and impacts of anxiety experienced by juvenile inmates prior to release at LPKA Class I A Kupang. This research employed a descriptive qualitative approach. The study population consisted of 38 juvenile inmates, from which five were selected as primary informants using purposive sampling based on specific inclusion criteria, such as age and readiness for release. In addition, two rehabilitation officers were interviewed as triangulation informants to strengthen data validity and provide additional perspectives. Data were collected through in-depth interviews and analyzed using the Miles, Huberman, and Saldaña model, involving data reduction, data display, and conclusion drawing. The results indicate that the anxiety experienced by juvenile inmates before release is influenced by young age, low educational background, past traumatic experiences, weak self-concept, and introverted personality types. The most dominant form of anxiety found was neurotic anxiety. The most common response was moderate anxiety, characterized by behavioral and emotional symptoms such as restlessness, sleep disturbances, and excessive worry about the future. The most visible impact was mood-related symptoms, including irritability and social withdrawal. In conclusion, the most dominant cause of anxiety was the lack of knowledge and experience in preparing for the future, worsened by gender-related tendencies in boys to suppress emotions and their generally lower level of formal education. Therefore, further research and rehabilitation programs should focus on enhancing children's capacity through life skills training, sustained emotional support, and the provision of concrete information on post-release educational and employment opportunities to better equip juvenile inmates for reintegration into society.